THE PROBLEM OF CHOICE BETWEEN TRUTH AND A LIE IN THE PLAYS BY VOLODYMYR VYNNYCHENKO “LIE” AND BY JERZY SZANIAWSKI “ŻEGLARZ (SAILOR)” - Кузнєцова, Г. Г. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
From the perspective of typological comparisons, the article deals with the dichotomy of the terms ‘truth – lie’ and ‘fact – myth’ in the plays by the Ukrainian and Polish playwrights. Moral and ethical representations are revealed in terms of interpersonal collisions between the characters, and the justification of their actions and behaviour.